Pengaruh Kamus Digital terhadap Penguasaan Kosa Kata Bahasa Inggris - Resti CItra Dewi; Supriadi (JURNAL INFORMATIKA DAN PERANCANGAN SISTEM (JIPS), 2022)
The use of English is one of the demands because English is used to communicate with people in the world. Then, how to improve English vocabulary? One of the best ways to improve speaking is through reading a lot of material and mastering English Vocabulary, so communication skills go hand in hand. After analyzing the data in this study, the results showed that students who were taught using digital dictionaries had an effect on students' English vocabulary mastery than those taught using conventional dictionaries. In this case, students who have devices such as smartphones can be used to support the learning process such as using a digital dictionary that can be downloaded from an application, because it is easy and practical to use can certainly increase the willingness to learn English vocabulary.